KETUHANAN DALAM FILSAFAT HINDU - Prasanthy Devi Maheswari; I Ketut Donder (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Everyone has a desire to understand God. But not a single human can show any evidence that they have seen God or heard God speak to them. After understanding the essence of God, even though they wanted to express their experience of seeking God, it was still very difficult for them to express God in words. A wise man said, don't argue about God with your mind, because God is as many as human thoughts. So this research aims to provide a way of understanding God in a wise way according to the essence of studying philosophy. This research is a qualitative research that uses descriptive analysis method with library research techniques, and a Hindu divinity philosophy approach, namely the search for God by speculating radical philosophical thoughts according to Vedānta. The philosophy of God in this study refers to the Upanișad literature. As an effort to understand God which is the essence of the highest reality through reason. God is understood through formal objects and material objects of philosophy, which are formulated through logical arguments in the Upanișads. The final result in the search for divinity within oneself is attaining Self-Realization while living in the world (Jivanmukti). It is also said to be the eternal bliss that results from meeting God in the mind. Enjoying the peace of God created by thought is the result of practice. Discussion of God in philosophy will never judge other people's thought processes in understanding God, because everyone will meet God according to their own thoughts and thought processes. That is the correct way of seeking God based on the Philosophy of God.